Crescimento e distribuição de renda - Ribeiro, Ricardo Luiz Mendes (1994)
The present dissertation has as main purpose to discuss the relations between growth and income distribution. First, I show how c1assical, neoclassical and keynesian tradicional approaches point to the existence of a trade-off between growth and income distribution. After that, three different models were presented based on Bresser Pereira (1986), Lucas (1988), and Dutt (1984,1987) and Amadeo (1986). These models allow the conc1usion that there is not a necessary trade-offbetween growth and income distribution, We also present a hyphothesis that this relation depends on the levei of economic development of a country. In the ealier stages of development, the trade-off exists, but, since the country reaches more advanced stages of development, this relation changes and the presence of a high income concentration pattern becomes an adicional barrier to development